2013
DOI: 10.1155/2013/526949
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Self-Care Behaviors and Related Factors in a Rural Hypertension Population: A Questionnaire Survey

Abstract: The objective of this study was to investigate the self-care behaviors among hypertensive patients in primary care. A cross-sectional survey, with 318 hypertensive patients, was conducted in a rural area in Beijing, China, in 2012. Participants were mainly recruited from a community health clinic and completed questionnaires assessing their self-care behaviors, including data on adherence to a prescribed medication regimen, low-salt diet intake, smoking habits, alcohol consumption, blood pressure monitoring, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
83
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 29 publications
(30 reference statements)
14
83
6
Order By: Relevance
“…Sodium reduction associated with other dietary recommendations has been shown to be effective in reducing blood pressure levels (Bray et al, 2004;He et al, 2013;Sacks et al, 2001), although no effect of sodium reduction on cardiovascular or overall mortality has been found (DiNicolantonio et al, 2013;Taylor et al, 2011). In this study, only a small number of participants diagnosed with hypertension reported being on a low salt diet, a value lower than reported in other studies (Hu et al, 2013;Warren-Findlow and Seymour, 2011). A possible explanation is the difficulty in implementing low salt diets (He and MacGregor, 2010).…”
Section: Hypertensioncontrasting
confidence: 50%
“…Sodium reduction associated with other dietary recommendations has been shown to be effective in reducing blood pressure levels (Bray et al, 2004;He et al, 2013;Sacks et al, 2001), although no effect of sodium reduction on cardiovascular or overall mortality has been found (DiNicolantonio et al, 2013;Taylor et al, 2011). In this study, only a small number of participants diagnosed with hypertension reported being on a low salt diet, a value lower than reported in other studies (Hu et al, 2013;Warren-Findlow and Seymour, 2011). A possible explanation is the difficulty in implementing low salt diets (He and MacGregor, 2010).…”
Section: Hypertensioncontrasting
confidence: 50%
“…[13][14][15][16] Moreover, financial and geographical accessibility of the available health institutions, the accessibility, and clinical practice of clinicians such as nurses and physicians together with the presence of essential medicines have been reported as essential factors in the control of high BP among health service-related factors. 15,16 Although attention has been given on processing strategies that improve adherence to treatment regimens like self-care behaviors for better BP control, [17][18][19] majority of the patients in health care facility received medication but not lifestyle education, indicating partial adherence to JNC7 guidelines. For instance, on average, only 30% of hypertension patients practice lifestyle modifications as a treatment of hypertension.…”
Section: Tesfaye Et Almentioning
confidence: 99%
“…This is because, ownership of a BP machine reinforces the practice of SMBP. Hence, several studies posit that most patients depend on patent medicine dealers, nurses and pharmacist for home monitoring of blood pressure 6,8,9 and this accounts for about 37.5% 10 and 67.2% 11 of SMBP practices in patients .…”
Section: Discussionmentioning
confidence: 99%
“…This correlated with similar studies which showed that higher socioeconomic status and higher level of education were associated with better practice of SMBP. 2,6,7,8,9,10 . This relationship is worrisome especially in developing countries and other resource poor settings where optimal hypertension management may be hampered by economic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation